Comparative efficacy of intravenous versus intravenous combined with intrathecal/intracerebral ventricle injection of polymyxin B for Acinetobacter baumannii intracranial infection: A retrospective study - Li You; Ru-meng Ding; Ting-ting Liu; Hai-yang Meng; Duo-lu Li (Journal of Global Antimicrobial Resistance, 2025)
Objective: Intracranial infections caused by Acinetobacter baumannii (A. baumannii) are common and life-threatening. This study aimed to compare the clinical efficacy and risk factors associated with 30-d mortality rates between intravenous (IV) polymyxin B and a combination of intravenous (IV) with intrathecal (IVT)/intracerebral (ITH) polymyxin B in the treatment of this type of intracranial infection. Methods: This retrospective study analysed patients with A. baumannii intracranial infections treated from November 2018 to March 2023. Based on the established inclusion and exclusion criteria, 57 patients were included in the study. Patients treated with IV polymyxin B combined with IVT/ITH polymyxin B were assigned to the IV plus IVT/ITH group, while those treated solely with IV polymyxin B were assigned to the IV group. Baseline characteristics and treatment outcomes were systematically collected and analysed. Kaplan-Meier survival analysis and multivariate logistic regression analysis were performed. Results: The study involved 57 patients who acquired A. baumannii intracranial infection. The cure rate was 31.6% (18/57) and a 30-d mortality rate of 33.3% (19/57). Compared to the IV group, the IV plus IVT/ITH group demonstrated a higher cure rate (15.4% vs. 45.2%, P = 0.034) and lower 30-d mortality (50.0% vs. 19.4%, P = 0.015). Multivariate logistic regression analysis indicated that the absence of IVT/ITH polymyxin B (P = 0.043) and the preexisting renal insufficiency at admission (P = 0.027) were independently associated with increased 30-d mortality. Conclusions: The combination of IV and IVT/ITH polymyxin B administration represents an effective therapeutic strategy for A. baumannii infections, demonstrating higher cure rates, significantly reduced 30-d mortality, and a substantial survival advantage. Notably, ITH/IVT treatment does not appear to increase the incidence of neurotoxicity. However, the true incidence of neurotoxicity associated with IVT/ITH polymyxin B may be underestimated.